Interspecific competition enhances nitrogen fixation in an actinorhizal shrub - Hagan, Donald L; Jose, Shibu (Plant ecology, 2011)
In forest understory restoration, the establishment of reintroduced species may be strongly linked to their ability to compete for belowground resources. In this study, we provide isotopic and morphological evidence for competition-induced increases in nitrogen fixation by Morella cerifera (L.) Small (wax myrtle) when planted with Pinus palustris Mill (longleaf pine). Compared to a competition-free treatment, we found no significant differences in tissue N concentrations for M. cerifera. However, ¹⁵N enrichment in leaves, stems and roots, as well as whole-plant values for nitrogen derived from fertilizer were significantly lower when the plants were subject to interspecific competition from P. palustris. Plants in the competition treatment also allocated a significantly greater percentage of belowground biomass to root nodules than those in the competition-free treatment (0.65 vs. 0.41%). This strongly suggests that M. cerifera is capable of upregulating nitrogen fixation in response to interspecific competition. This may help explain why M. cerifera outperformed non-nitrogen-fixing species reintroduced on the same site.